Antimicrobial Susceptibility of Commensal Escherichia coli from Pig Fecal Samples and Enhanced Sensitivity for Direct Detection of the blaCTX-M Gene by Nested PCR - Nutchaba Suchanta; Naeem Ullah; Pitak Santanirand; Nutthee Am-In; Nuntaree Chaichanawongsaroj (Animals)
The commensal Escherichia coli in the gut of pigs is a major reservoir of antimicrobial resistance and can result in possible transmission to humans through the food chain. Direct detection of E. coli from fecal samples is challenging and can be used as a bioindicator of antimicrobial resistance. This study aimed to compare the antimicrobial susceptibility profiles in commensal E. coli from antibiotic- and nonantibiotic-using pig farms and developed the direct detection of ESBL genes in pig fecal samples using nested PCR (nPCR) and multiplex PCR (mPCR) techniques. All direct genotypic results were validated with the results of PCR sequencing of isolated E. coli colonies. The ESBL-producing E. coli were found in 98.6% (145 isolates) and 96.6% (144 isolates) of antibiotic-using and nonantibiotic-using farms, respectively, predominantly CTX-M-55. The nPCR decreased the limit of detection (LOD) from sPCR about 100 times, and the lower LODs of 102, 101, and 1 CFU/mL were reached after incubating samples in an enrichment medium for 2, 4, and 8 h, respectively. The mPCR, sPCR, and nPCR techniques showed sensitivities of 30.15%, 69.85%, and 91.91%, respectively, compared to PCR sequencing. The stability and recycling of ESBL genes were independent of antibiotic usage in commensal E. coli originating in pig farms.